2017
DOI: 10.3390/nu9060612
|View full text |Cite
|
Sign up to set email alerts
|

Know Your Noodles! Assessing Variations in Sodium Content of Instant Noodles across Countries

Abstract: Reducing salt intake is a cost-effective public health intervention to reduce the global burden of non-communicable disease (NCDs). Ultra-processed foods contribute ~80% of dietary salt in high income countries, and are becoming prominent in low-middle income countries. Instant noodle consumption is particularly high in the Asia Pacific region. The aim of this study was to compare the sodium content of instant noodles sold worldwide to identify potential for reformulation. Analysis was undertaken for 765 insta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 17 publications
(22 reference statements)
3
20
0
1
Order By: Relevance
“…The present study not only addressed this bias but also went a step further by also ensuring comparability within the categories, for example, by performing analyses with and without reduced-salt products, and by excluding powder products in predominantly liquid categories (eg, in chilli sauces) and vice-versa (eg, in stocks). Additionally, our findings also align with those of Farrand et al , who observed that a higher proportion of products met salt targets in countries where targets were set in comparison to countries without targets 13…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The present study not only addressed this bias but also went a step further by also ensuring comparability within the categories, for example, by performing analyses with and without reduced-salt products, and by excluding powder products in predominantly liquid categories (eg, in chilli sauces) and vice-versa (eg, in stocks). Additionally, our findings also align with those of Farrand et al , who observed that a higher proportion of products met salt targets in countries where targets were set in comparison to countries without targets 13…”
Section: Discussionsupporting
confidence: 91%
“…The results of our between-country analyses are also concordant with those of previous studies, where products sold in China usually contained more salt than those found on the UK market 13 14. In Huang et al ’s food group-level comparison, 77% of the products they included in the food group ‘Sauces and spreads’ were cooking sauces, gravies and stocks in China (categories known to have higher salt content than other sauces), compared with 55% in the UK 14.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, an observational study by Farrand et al . in 10 Asian countries such as China, Indonesia and India, also demonstrated that the mean salt content per 100 g of instant noodles was high at 4.86, 4.79 and 2.28 g, respectively 25. In this same study, Farrand et al .…”
Section: Introductionmentioning
confidence: 54%
“…In this same study, Farrand et al . also reported that two-thirds of the Asian countries in the study had <55% instant noodle products that meet the Pacific Salt Reduction Target (4 g/100 g of salt) 25 26…”
Section: Introductionmentioning
confidence: 87%